2019
DOI: 10.3390/genes10080605
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Acid-Responsive Genes and Pathways Involved in Polyamine Regulation in Iron Walnut

Abstract: We reported changes in the co-regulated mRNA expression in iron walnut (Juglans sigillata) in response to soil pH treatments and identified mRNAs specific to acidic soil conditions. Phenotypic and physiological analyses revealed that iron walnut growth was greater for the pH 4–5 and pH 5–6 treatments than for the pH 3–4 and pH 6–7 treatments. A total of 2768 differentially expressed genes were detected and categorized into 12 clusters by Short Time-series Expression Miner (STEM). The 994 low-expression genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This study shows that sugar beet has the best growth state in high pH environment, and low soil pH affects sugar beet photosynthesis. Similarly, phenotypic and physiological analyses revealed that the optimum pH of iron walnut was 4-5 ( Luo and Liu, 2019 ), and the net photosynthetic rate significantly declined under non-optimal pH conditions. Moreover, it has recently been reported that low pH affected ROS and MG metabolisms in Citrus roots and leaves, and the negative effect was more significant in roots than in leaves ( Long et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that sugar beet has the best growth state in high pH environment, and low soil pH affects sugar beet photosynthesis. Similarly, phenotypic and physiological analyses revealed that the optimum pH of iron walnut was 4-5 ( Luo and Liu, 2019 ), and the net photosynthetic rate significantly declined under non-optimal pH conditions. Moreover, it has recently been reported that low pH affected ROS and MG metabolisms in Citrus roots and leaves, and the negative effect was more significant in roots than in leaves ( Long et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that iron walnut growth was better in pH 4-5 and pH 5-6 treatments than in pH 3-4 and pH 6-7 treatments. Transcriptome analyses revealed that the pathways involved in polyamine metabolisms participated in iron walnut acid stress tolerance ( Luo and Liu, 2019 ). Moreover, under alkaline conditions, high rhizosphere pH inhibits plant growth by imposing an adverse effect on roots elongation and disrupting cellular ionic homeostasis and pH.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the genomic data for walnut (J. regia and J. sigillata) available from the NCBI (Martinez-Garcia et al, 2016;Luo and Liu, 2019b), 21 pairs of primers (Table 2) were obtained after two rounds of screening. Then, the fluorescent amplification products were sequenced on an ABI 3730 DNA analyser (Applied Biosystems), and allele sizing was performed using Gene Mapper™ 4.1 software (Applied Biosystems).…”
Section: Ssr Analysismentioning
confidence: 99%
“…We performed cluster analysis of the DEGs in IVF and PA by using the short time-series expression miner (Stem) software (Luo and Liu, 2019). We performed functional annotation and enrichment analysis in each group for the nine clusters with p-value < 0.01 in IVF and PA, respectively ( Figure 1B, Figure 2).…”
Section: Differential Expression Analysis Of Mrnas In Adjacent Stagesmentioning
confidence: 99%